2014
DOI: 10.1089/neu.2013.3144
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reveals White Matter Injury in a Rat Model of Repetitive Blast-Induced Traumatic Brain Injury

Abstract: Blast-induced traumatic brain injury (bTBI) is one of the most common combat-related injuries seen in U.S. military personnel, yet relatively little is known about the underlying mechanisms of injury. In particular, the effects of the primary blast pressure wave are poorly understood. Animal models have proven invaluable for the study of primary bTBI, because it rarely occurs in isolation in human subjects. Even less is known about the effects of repeated primary blast wave exposure, but existing data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 69 publications
(88 reference statements)
8
46
1
Order By: Relevance
“…The anatomical locations of low FA using tract specific analysis and tract profile analysis in this study are also consistent with the results from using mechanical simulation and finite element analysis of brain exposure to blasts, showing that the highest level of axonal shear/ strain effects developed in the regions of corpus callosum and corona radiata [Chatelin et al, 2011] in mTBI model. Secondary brain injury and repair mechanisms such as chronic inflammation and hypermetabolism may sensitize the brain to the subsequent injury [Calabrese et al, 2014], leading to axonal repair, reactive gliosis [Glushakova et al, 2014;Johnson et al, 2013;Kiraly and Kiraly, 2007] or irreversible axonal damage [Gupta and Przekwas, 2013]. Our findings of the inverse relationship between postinjury duration and FA over the cingulum bundles (Fig.…”
Section: Group Analysismentioning
confidence: 68%
“…The anatomical locations of low FA using tract specific analysis and tract profile analysis in this study are also consistent with the results from using mechanical simulation and finite element analysis of brain exposure to blasts, showing that the highest level of axonal shear/ strain effects developed in the regions of corpus callosum and corona radiata [Chatelin et al, 2011] in mTBI model. Secondary brain injury and repair mechanisms such as chronic inflammation and hypermetabolism may sensitize the brain to the subsequent injury [Calabrese et al, 2014], leading to axonal repair, reactive gliosis [Glushakova et al, 2014;Johnson et al, 2013;Kiraly and Kiraly, 2007] or irreversible axonal damage [Gupta and Przekwas, 2013]. Our findings of the inverse relationship between postinjury duration and FA over the cingulum bundles (Fig.…”
Section: Group Analysismentioning
confidence: 68%
“…Among the leading complaints are sleep and emotional disturbances as well as altered sensory sensitivities, both auditory and visual 14 . Cerebellar abnormalities have been found in most human bTBI imaging studies 12,15,16,43 and in a recent rodent bTBI study 24 . These findings illustrate the region-specific vulnerability of the brain to different types of physical insults-an important albeit poorly understood issue in TBI.…”
Section: Discussionmentioning
confidence: 93%
“…However, only a limited number of clinical studies included readouts at several post-injury time points in Veterans [11][12][13][14][15][16][17] . DTI's sensitivity relative to conventional imaging tools has prompted its recent use in experimental mTBI [18][19][20] with a few rodent blast-induced TBI (bTBI) studies [21][22][23][24] . These studies identified a number of brain regions, including the hippocampus and the cerebellum, as being affected in mbTBI 25 .…”
mentioning
confidence: 99%
“…Figure 7 demonstrates an example that exploits all of the pipelines discussed thus far. The study was designed to understand the mechanism of blast-induced traumatic brain injury (bTBI) in a rat model using DTI magnetic resonance histology 11 . The study tested the hypothesis that an initial blast injury might sensitize the animal to a second injury.…”
Section: Resultsmentioning
confidence: 99%